Op de bres voor het „Deutschtum“ in Limburg (1933–1940) - Brauer, Jan (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2023)
„Borders engender cultural and socio-political interaction between states. Especially in border regions, issues of nationality and identity sharpen in times of political tension. As early as 1933, for instance, Limburg faced strong influence of the rising National Socialist Third Reich, partly because of the many thousands of German migrants - ‘Rijksduitsers’ - who lived and worked there. Fierce propaganda and intimidation had to activate these so-called ‘Volksgenossen’, but in addition, the Limburgers, as ‘race-Germans’, also belonged in this Reich, according to Berlin. They had strayed from Deutschtum and had to be reclaimed with the use of propaganda. This early invasive socio-political influence process – a clear prelude to the occupation years ‘40-45’ – is examined in this article from German and Dutch sources. What was the impact on the daily lives of border residents, who traditionally fostered close ties with neighbours across the border? To answer this question, this article presents new cross-border regional research in the periphery of Limburg as a contribution to the broader historiography of Dutch WWII-history.“
Keywords: Grenzgebiet; Nationalsozialismus; Provinz Limburg (Niederlande)

Grensgevallen, vluchtelingen 1933–1940. Grenzfälle, Flüchtlinge 1933–1940 - Boersma, Ben; Eversdijk, Nicole P.; Jongejans, Jessie (Westmünsterland. Jahrbuch des Kreises Borken, 2010)
Keywords: Aalten; Ausstellung; Deutscher Flüchtling; Flüchtling; Grenzgebiet; Grenzüberschreitende Kooperation; Judenverfolgung; Kollektives Gedächtnis; Museum; Nationalsozialismus; Politische Verfolgung; Zweiter Weltkrieg

Dwangarbeid aan de grens. Regionale aspecten van de dwangarbeid in het grensgebied bij Aken in de nazi-tijd - Müller, Thomas (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Aachen (Region); Nationalsozialismus; Zwangsarbeit; Zweiter Weltkrieg

Reaktionen auf niederländische NS-Strömungen und deutsche Einflüsse. Beobachtungen zum Doetinchemer Gemeinderat ab 1935 - Volker, Inge (Nationalsozialistische Herrschaft und Besatzungszeit. Historische Erfahrung und Verarbeitung aus niederländischer und deutscher Sicht, 2000)
Keywords: Doetinchem; Gemeinderat; Grenzgebiet; Kommunalpolitik; Nationaal-Socialistische Beweging der Nederlanden; Nationalsozialismus

Flucht über die Grenze. Die Hollandflucht im Dritten Reich über die niederländisch-westfälische Grenze und Kontrollmaßnahmen der Steuer- und Zollbehörden - Blumberg, Gerd (Unser Bocholt, 1995)
Keywords: Deutscher Flüchtling; Judenverfolgung; Nationalsozialismus; Politische Verfolgung; Westfalen; Zoll